Marriage Age Preference, Desire to Have Children, Children’s Value, and Family Readiness among Undergraduate Students of IPB University - Faradilla, Shania Af'ida; Sunarti, Euis (Journal of Family Sciences, 2024)
Family readiness is a way to measure a person's level of readiness to build a family and have children. This study aimed to analyze the influence of age preferences for marriage, desire to have children, and children's values ​​on family readiness among IPB students. This study was attended by 206 respondents, aged 19-24 years, who were unmarried. Data were collected online using purposive sampling. The results showed that marriage age preference ranged from to 24-25 years, most of the samples stated their strong desire to have children, and the children’s value and family readiness were in the moderate category. The correlation test showed that marriage age preference had a significant negative relationship with family readiness, while children’s values and desire to have children had a significant positive relationship with family readiness. The PLS test results show that children's values have a significant positive effect on family readiness. The higher the value of the benefits of children owned by a person, the higher their readiness to start a family. This study suggests that it is important for young adults to build positive communication with their parents to increase positive values ​​ for children and families.